Climate Change Adaptation Strategies Adopted for Sustainable Livelihoods by the Pastoral Community in Narok County - Korir, J. (Africa Environmental Review Journal, 2020)
Climate change is a global phenomenon that has posed complex challenges today. It is reported to impact negatively on both the economy and livelihoods of the population especially in the arid and semi-arid regions of Sub-Saharan Africa. Narok County in Kenya is one of the regions that has experienced extreme weather events characterised by changes in the rainfall patterns and increased frequency and intensity of droughts over the past 50 years (GOK 2010). These immense climatic conditions have threatened pastoral livelihoods in the County despite pastoralism having a great potential in contributing to household welfare. Despite this, no comprehensive studies have been conducted in the area on how the community can be involved in adaptation measures aimed at minimizing the effects of climate related shocks. The aim of this study was to assess and document efficient and effective adaptation strategies to climate change that are used by the pastoral community in Narok County in order to sustain their livelihoods. The author used descriptive survey design to achieve this objective while employing face to face interviews to collect primary data. The sample size comprised of 415 pastoral households identified through a multistage cluster sampling and simple random sampling techniques. The collected data was analysed using statistical package for social sciences (SPSS) computer program and results were presented in using tables and bar graphs. Findings showed that the main adaptation strategies used by the pastoral community include; crop cultivation, livestock diversification, destocking, water harvesting, soil conservation, tree planting, and irrigation farming, among others. Consequently, policies that incorporate indigenous knowledge, promote community-led adaptation, effective and appropriate dissemination of climaterelated information at the local level and those that provide access to relevant institutions should be formulated in order to enhance the resilience of pastoral communities to impacts of climate change.